Tax Knowledge, Taxpayer Awareness and Tax Service Quality on Taxpayer Compliance Moderated by Tax Sanctions - Subekti, Khalisah Visiana; Yuliana, Yuliana (Politeknik Ganesha Medan, 2024)
This research was conducted with the aim to find out whether there is influence from tax knowledge, taxpayer awareness and quality of tax services on motor vehicle taxpayer compliance in Magelang City which is moderated by tax sanctions. The sample used in this research is the taxpayers in the City of Magelang with a total of 249 respondents. The research method in this study is a quantitative approach method and the data obtained from distributing questionnaires via Google form. Data processing was carried out using the SmartPLS application version 4.0.9.4 with the aim of testing the hypothesis. The results obtained in this study are tax knowledge, taxpayer awareness, and tax service quality have a positive effect on taxpayer compliance in paying motor vehicle taxes. Tax Knowledge can increase taxpayer compliance because the more taxpayers understand the purpose of taxes and how to pay taxes and sanctions when they do not pay taxes, the more taxpayers will be aware of paying taxes. Taxpayer awareness is a condition in which the taxpayer knows, understands and implements tax provisions voluntarily, so the higher the level of taxpayer awareness, the better so as to increase taxpayer compliance. Good quality tax services can create satisfaction and success in paying taxes so as to increase taxpayer compliance. Tax sanctions can also strengthen the relationship between tax knowledge, taxpayer awareness, quality of tax services on taxpayer compliance because the higher or heavier the tax sanctions, the higher the level of taxpayer compliance.